2015
DOI: 10.5693/djo.01.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Retinal detachments after Boston Keratoprosthesis: incidence, predisposing factors, and visual outcomes

Abstract: Purpose-To determine the rates, predisposing factors, and visual outcomes of retinal detachment (RD) after Boston Keratoprosthesis (KPro) implantation.Methods-In this noncomparative, interventional case series, the medical records of 170 patients (205 eyes) who underwent Boston type 1 and type 2 KPro implantation at the Massachusetts Eye and Ear Infirmary between April 1993 and June 2009 were retrospectively reviewed. Incidence and annual rates of RD were calculated, and the roles of possible predictive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…Retinal detachment was observed in two patients of the present study. Patients with underlying autoimmune systemic disorders should be closely monitored for the development of retinal detachment following KPro surgery (33). In the present study, corneal melting occurred in two patients (10%), the rate of which was decreased compared with that reported by Cade et al (34).…”
Section: Discussionsupporting
confidence: 40%
“…Retinal detachment was observed in two patients of the present study. Patients with underlying autoimmune systemic disorders should be closely monitored for the development of retinal detachment following KPro surgery (33). In the present study, corneal melting occurred in two patients (10%), the rate of which was decreased compared with that reported by Cade et al (34).…”
Section: Discussionsupporting
confidence: 40%
“…Such a situation is likely to get worse with every subsequent surgical procedure, including a B-KPro. It can result in RPM, vitreous opacities, cystoid macular edema, epiretinal membrane, or-worst of all-a retinal detachment, which has a poor record of repair [40,46,65]. Again, autoimmune disease is the leading risk factor.…”
Section: Infections Prophylaxismentioning
confidence: 96%
“…21 Vitreous inflammation can lead to posterior vitreous detachment with subsequent retinal breaks, and idiopathic vitritis is a reported risk factor for RD after KPro. 4,21,22 Idiopathic vitritis occurred frequently in our series, but detailed risk factor analysis was not performed because of the small cohort size and is reported elsewhere. 4 It has also been shown that a chronic low grade of inflammation from the KPro device itself can promote a strong inflammatory response within the retina, leading to an aggressive PVR response following RD.…”
Section: Discussionmentioning
confidence: 99%